Redefining Shiga toxin–induced human cell death as NLRP1- and gasdermin E-mediated pyroptosis - Rafael Ricci-Azevedo; Bishajit Sarkar; Sonia Shivcharan; Aadrita Hazra; Mercy Browne; Emma K. Carlson; Udayan Chidambaram; Vijay A. Rathinam; Sivapriya Kailasan Vanaja (Proceedings of the National Academy of Sciences, 2026)
Shiga toxin (Stx)–mediated hemolytic uremic syndrome (HUS) prevails as the leading cause of pediatric renal failure worldwide despite decades of efforts to develop therapeutic strategies. Stx killing of large populations of sensitive cells in the vasculature and kidney underlies HUS development. However, the exact nature of Stx-induced cell death and its mechanism are not clear. Here, we demonstrate that Stx-induced cell death in several HUS-relevant human cells, such as kidney epithelial cells, podocytes, and human intestinal microvascular endothelial cells, is pyroptosis, an inflammatory form of cell death. Remarkably, our findings identify gasdermin E (GSDME) activation as the cardinal event that mediates Stx killing of human cells. Mechanistically, Stx activates, through ribotoxic stress, a caspase-8-caspase-3 pathway that licenses GSDME-dependent pyroptosis of susceptible cells. Intriguingly, NLRP1 amplifies this pyroptotic pathway in certain Stx-sensitive cells by promoting caspase-8 activation. Together, our findings define the nature and mechanism of a bacterial toxin-induced cell death, providing crucial insights into pathogenic determinants of a critical pediatric illness.